Novel pentadecyl phenol-tagged L-tryptophan molecules: synthesis, self- assembly and liquid crystalline properties - Parappurath, Akhil; Abraham, Jancy Nixon (Chemistryselect, 2018)
The paper describes the self-assembly and liquid crystalline properties of pentadecylphenol tagged L-tryptophan molecules having ester and amide functionality. We have synthesized a series of molecules having mono and ditryptophan moieties attached to pentadecylphenol through amide or ester linkage. The fluorescence properties of the Boc-L-tryptophan-pentadecylphenol molecules were measured in methanol and found to aggregate beyond the critical aggregation concentration and self-assembled to give spherical structures. Upon deprotection of Boc group, the amine end group got involved in extended hydrogen bonding and fibril like structures were developed. These molecules also showed liquid crystalline behavior in hydrogen bonding solvents such as benzyl alcohol and showed needle like crystals in tert-butanol, as analyzed by polarized optical light microscopy.
Keywords: Cardanol; liquid crystalline; pentadecylphenol; Self-assembly; Tryptophan

Self-assembly of Di-guanine peptide nucleic acid amphiphiles into fractal patterns - Abraham, Jancy N.; Pawar, Prabhakar; Kootteri, Dilna K. (ChemistrySelect, 2019)
Peptide nucleic acids (PNAs) amphiphiles have been reported to assemble into different nanostructures; however, there is immense untapped potential to control their supramolecular assemblies by altering their lipid chain. Here, we functionalized di-guanine PNA with various hydrophobic appendages, namely dodecyl, p-dodecylbenzoyl and pentadecyl phenol groups, to investigate the effect of aromatic linkers, long alkyl and alkoxyl substituents on hierarchical self-assembly of di-guanine PNA. Systematic electron microscopy and atomic force microscopy studies revealed that while all three derivatives of di-guanine-PNA formed nanospheres, only nanospheres of dodecylamide and pentadecyl phenol derivatives matured into nanorods, these later formed higher order fractal assemblies. Furthermore, we observed that inclusion of a positively charged lysine at the C-terminus prevented fractal assembly, possibly due to electrostatic repulsion between the head groups. Thus, the findings of the present work might guide rational design of PNA amphiphiles to obtain specific self-assembled morphology.
Keywords: Fractal pattern; Guanine; pentadecylphenol; Peptide nucleic acid; Self-assembly